Customer Centric in Hospitality Industry: a Systematic Literature Review and Future Research Direction - Rini, Gilang Puspita; Ferdinand, Augusty Tae (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
The purpose of this research is to review the literature published from 2010 to 2020 regarding customer-centric strategy in the context of the hospitality industry. The customer-centric paradigm focuses on creating value for its customers, so it becomes interesting to study in the context of hospitality. This is a literature review research with the Publish or Perish software used to obtain initial data from a total of 235 articles published from 2010-2020 according to the Scopus database. The articles were further analyzed according to the criteria, with only 87 articles. The results showed that a customer-centric strategy is a company strategy that pays attention to consumer wants and needs. The customer-centric approach is similar to the outside-in approach because they pay attention to customers and adjust their complaints to company policies and strategies. This research provides benefits for future studies on customer-centric strategy in the hospitality industry that uses big data analytics to create value for customers. Furthermore, it provides an overview of customer-centric strategy trends in terms of understanding, theoretical perspective, and setting needed for future studies.